for the first one, since 2+e^2 is a constant, you simply get
f'(x) = (2+e^2)(2x + 1/x)
(are you sure there was no typo ?)
for the 2nd use the quotient rule, give it a try, let me know what you got
f(x) (x^2+lnx)(2+e^2)
derivative
also,
f(x)= (3x+x^4)^(3/2)/(7x^2-1)
3 answers
the first one should be (x^2+lnx)(2+e^x) sorry
f(x) = (x^2+lnx)(2+e^x)
f'(x) = (x^2 + lnx)(e^x) + (2+e^x)(2x + 1/x)
I used the product rule,
expand and simplify if needed
f'(x) = (x^2 + lnx)(e^x) + (2+e^x)(2x + 1/x)
I used the product rule,
expand and simplify if needed